COMO ENTENDER HEIDEGGER? OS TEOREMAS DA DIFERENÇA ONTOLÓGICA E DO CÍRCULO HERMENÊUTICO - Cleyson de Moraes Mello (TRF2, 2018)
Heidegger's philosophical hermeneutics takes on a transformative bias. Hence the need to understand the theorems of ontological difference and the hermeneutic circle from being-in-the-world. It is in this sense that, given the striking ineffectiveness of classical hermeneutics, methodological in your origin, it is necessary to construct a theoretical strength that point to the construction of the conditions of possibility of understanding the sense, as a way of being-in-the-world.